Impact of Haemodialysis on Coagulation Profile in Chronic Kidney Disease - Raja, Veena; Ganapathy, Shivashekar; Karthikean, Suresh Kumar; Das Prakash, Pradhiksha (Annals of Pathology and Laboratory Medicine, 2021)
Background Chronic kidney disease (CKD) with its high prevalence, morbidity and mortality is an important public health problem. Considering the nature of the haemodialysis process, it has a considerable impact on the coagulation profile. To find out the variations in Platelet count, Prothrombin time (PT), International Normalised Ratio (INR) and Activated Partial Thromboplastin Time (aPTT) before and after haemodialysis patients. Materials and Methods: This prospective observational study of Coagulation profile and platelet count in pre and post hemodialysis patients with chronic renal failure was conducted on 150 CKD patients in the Department of Pathology, SRM Medical College Hospital & Research Centre. p value <0.05 was considered to be statistically significant. Results In this study, there was significant reduction in platelet count from mean 2.29 cells/cu.mm in pre dialysis to 2.03 cell/cu.mm in post dialysis. There was a significant prolongation in both PT and aPTT values in post dialysis Conclusion These findings expose CKD patients to higher risk of bleeding disorders, which may have a role in increasing the rate of patient mortality and morbidity. In the light of this study, there is a need for nephrologist to monitor the coagulation profile and platelet count of CKD patients on dialysis, and treat any derangements in the same, so as to improve outcome for these patients.